Air pressure effects on biomass yield of two different Kluyveromyces strains - Pinheiro, Rita (2000)
The use of air pressure as a way of improving oxygen transfer in aerobic bioreactors was investigated. To compare the air pressure effects with traditional air bubbled cultures, experiments using a pressure reactor and a stirred flask, with the same oxygen transfer rate, were made. Kluyveromyces marxianus is an important industrial yeast and some of it show a “Kluyver effect” for lactose: even under oxygen limited growth conditions, certain disaccharides that support aerobic, respiratory growth, are not fermented. This study deals with the effect of increased pressure on the physiological behavior of two Kluyveromyces strains: K. marxianus ATCC10022 is a lactose-fermenting strain, whereas K. marxianus CBS 7894 has a Kluyver-effect for lactose. For K. marxianus ATCC10022 an air pressure increase of 2 bar led to a 3-fold increase in biomass yield. When air pressure increased an enhancement of ethanol oxidation of cell yeasts was also observed. Batch cultures of K. marxianus CBS 7894 exhibited different growth behaviour. Its metabolism was always oxidative and ethanol was never produced. With the increase in air pressure, it was possible to increase the productivity in biomass of K. marxianus CBS 7894. As a response to high oxygen concentrations, due to the increase in oxygen partial pressure, oxidative stress in the cells was also studied. Antioxidant defences, such as superoxide dismutase, catalase, and glutathione reductase, were at high activity levels, suggesting that these yeast strains could tolerate the increased pressures applied.